Electroacupuncture for the treatment of frozen shoulder: A systematic review and meta-analysis - Heo, Jeong-Weon; Jo, Jeong-Hun; Lee, Jung-Ju; Kang, Hee; Choi, Tae-Young; Lee, Myeong Soo; Kim, Jong-In (Frontiers in Medicine, 2022)
Background: Electroacupuncture (EA) has reportedly been successful in controlling pain, but there have been no systematic reviews examining the impact of EA on patients with frozen shoulder (FS). The purpose of this review is to provide evidence on the safety and efficacy of EA for pain management in patients with FS. Methods: We searched eleven databases from their inception: EMBASE, the Cochrane Library, PubMed, AMED, one Chinese medical database, and six Korean medical databases. Two researchers independently performed the study selection, data extraction, and assessment. Bias-related risk was evaluated using the Cochrane risk-of-bias assessment tool. Results: This review included thirteen studies involving 936 patients. The EA group exhibited improvements in FS pain (MD −1.11, 95% CI −1.61 to −0.61, p < 0.0001, I2 = 97%), function (SMD 2.02, 95% CI 0.36 to 3.69, p < 0.00001, I2 = 97%), and response rates (RR 1.16, 95% CI 1.07 to 1.25; p = 0.0002; I2 = 0%) over the manual acupuncture (MA) group. As an adjunct treatment, EA improved FS pain (SMD -1.12, 95% CI -1.52 to -0.71, P<0.00001, I2 = 0) compared to the control treatments. No adverse effects were reported. Conclusion: EA is reported to improve FS pain and function compared with control treatments. Additionally, EA can be used as an adjunct therapy for FS pain. EA could emerge as a potent intervention against FS.